The need for anti-corruption policies in developing countries. Issue 1 (15th July 2020) - Brody, Richard G.; Gupta, Gaurav; Ekofo, Angela N.; Ogunade, Kehinde Mayokun
Abstract : Purpose: In this study, the authors examine the issue of corruption in the government institutions of developing countries. Additionally, this study aims to answer the following research question: How do developing countries implement and enforce these anti-corruption policies? Specifically, the authors look at the laws adopted in different developing countries to deal with issues related to corruption. Design/methodology/approach: The authors use the qualitative approach to examine the causes of recent corruption among government officials in developing countries such as Nigeria, India, the Democratic Republic of Congo and Uganda. A comparative approach was used to compare and contrast the anti-corruption practices of developing and developed countries. Findings: The findings indicate that corruption is rampant in much of the developing world. On a positive note, the authors have found evidence of actions taken by governments in these developing economies to rapidly deal with issues of corruption. All the countries analyzed in this paper have developed anti-corruption policies and related acts to detect and punish the perpetrators of corruption. Originality/value: This paper provides a greater insight as to how the anti-corruption policies are formulated and enforced in the developing world. Specifically, the authors provide examples of different emerging countries and their approaches to developing and enforcing anti-corruption policies. This guidance can help others around the world to deal with anti-corruption policies in their countries. Although the authors have learned a lot about the detrimental effects of corruption and laws enacted to combat it, the next step is to examine the processes used by the developing countries to develop these anti-corruption laws and policies.